Evaluating Breakdown of Wheel Loader Heavy Equipment Using Failure Mode and Effect Critical Analysis Method - Rizqika , Agung Qiu; Mahbubah, Nina (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2022)
Autonomous maintenance is considered a comprehensive approach to detecting machine and equipment breakdown. PT. A is an enterprise engaged in heavy equipment services. Even though the company has implemented autonomous maintenance management, there has been damage and operational failure of the wheel loader machine. A practical evaluation is needed to determine the breakdown's cause. This study aims to identify the causes of malfunctions or machine components to determine effective remedial measures. Failure Mode Effect and Criticality Analysis method is used as a research approach. This study begins by identifying the three most significant damage rankings, then calculating the highest level of critical value, using the Pareto diagram recommendation for improvement using the 5W + 1H analysis. The results showed three critical failure modes: the starter dynamo component with a value of 324, the main pump with a value of 288, and a radiator with 294. This study also instigates recommendations for improvements to minimize the factors that cause critical failure.